Dexamethasone, celecoxib, and simvastatin-induced 5-fluorouracil resistance in cancer cells: a possible role of lipid droplet accumulation - Sabbah, Duaa S.; Ikhmais, Balqis A.; Abdallah, Qasem M.; Phillips, Roger M.; Qinna, Nidal A. (Discover. Oncology, 2025)
Aim This study investigates the impact of dexamethasone (DEX), celecoxib (CXB), and simvastatin (SMV) on 5-fluorouracil (5-FU) resistance in cancer cells and their role in increasing lipid droplet (LD) accumulation. The study aims to assess how these non-anticancer drugs may influence the efficacy of 5-FU treatment, with potential implications for clinical outcomes. Methods Eight human cancer cell lines were treated with 5-FU alone and in combination with DEX, CXB, or SMV. LD levels were quantified using Oil Red O (ORO) staining, and cell viability was assessed with the sulforhodamine B (SRB) assay. Changes in LD levels and IC 50 values of 5-FU were analyzed to evaluate the impact of these drugs on 5-FU efficacy. Results Co-treatment of 5-FU with DEX, CXB, and SMV significantly increased LD accumulation across the tested cancer cell lines and induced resistance to 5-FU. The impact varied between cell lines, with some showing marked reductions in 5-FU efficacy when combined with these drugs. The observed increase in LDs may contribute to the reduced therapeutic effects of 5-FU, potentially compromising its clinical effectiveness. Conclusion The findings highlight that DEX, CXB, and SMV enhance 5-FU resistance by increasing LD accumulation, highlighting a critical, previously overlooked metabolic factor that may impact clinical treatment strategies and patient outcomes. If similar effects occur in clinical settings, the use of these drugs may need to be adjusted to avoid compromising cancer treatment efficacy. Further studies are warranted to evaluate this interaction and its implications in clinical practice.